Evolution of crystallographic phases in the system (Pb1-xCax)TiO3: A Rietveld study - Chandra A.; Pandey D. (My University, 2025)
X-ray powder diffraction studies on (Pb1-xCax)TiO3 ceramic powders revealed the presence of superlattice reflections due to antiphase and inphase tilts of oxygen octahedra for x ≥ 0.421. Rietveld analysis of the powder x-ray diffraction data confirmed that the structure of (Pb1-xCax)TiO3 is orthorhombic with Pbnm space group and a-a-c+ tilt system for x ≥ 0.421. For compositions with 0 < x ≤ 0.416, the structure was tetragonal, and the tetragonality decreased with increasing Ca2+ content.